2022
DOI: 10.2196/29422
|View full text |Cite
|
Sign up to set email alerts
|

Patient Influencers: The Next Frontier in Direct-to-Consumer Pharmaceutical Marketing

Abstract: Social media influencers are becoming an increasingly popular strategic communication tactic used across industry verticals, including entertainment, fashion, and beauty, to engage directly with consumers. Pharmaceutical companies have also recently entered the social media marketing arena and—within the bounds of governmental regulations—have found ways to build relationships directly with patients using covert persuasion tactics like partnering with social media influencers. Due to consumers’ negative percep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 71 publications
0
14
0
3
Order By: Relevance
“…Future research should also explore the role of social media and emerging technologies for pharmaceutical marketing. Willis and Delbaere (2022), for instance, encourage a research agenda on patient influencers on social media. Will these influencers create trustworthy connections with patients or further fuel skepticism?…”
Section: Possible Approaches To Reshaping Strategymentioning
confidence: 99%
“…Future research should also explore the role of social media and emerging technologies for pharmaceutical marketing. Willis and Delbaere (2022), for instance, encourage a research agenda on patient influencers on social media. Will these influencers create trustworthy connections with patients or further fuel skepticism?…”
Section: Possible Approaches To Reshaping Strategymentioning
confidence: 99%
“…3 An analogous system has emerged in which motivated companies for consumer medical products and devices create patient influencers. 4 These individuals may allow pharmaceutical entities to find loopholes around current laws controlling DTCA. Moreover, patient-to-patient promotion of a brand may engender more consumer trust and willingness to listen than direct company advertising campaigns.…”
Section: Invited Commentarymentioning
confidence: 99%
“…In the food industry, it has been demonstrated that child social media influencers generate millions of impressions for unhealthy food and beverage brands . An analogous system has emerged in which motivated companies for consumer medical products and devices create patient influencers . These individuals may allow pharmaceutical entities to find loopholes around current laws controlling DTCA.…”
mentioning
confidence: 99%
“…One such category that has long been thriving but only recently noticed by marketers is that of “patient influencers” [ 7 ]. Health Union defines patient influencers as “the most visible and trusted health consumers.…”
Section: Introductionmentioning
confidence: 99%